(untitled) - Food and Agriculture Organization of the United Nations (London, 2006)
The purpose of part B of the Code is to provide information on the design, construction, and equipment of fishing vessels with a view to promoting the safety of fishing vessels and safety and health of the crew. The Code is not a substitute for national laws and regulations nor is it a substitute for the provision of international instruments in relation to safety of fishing vessels and crew although it may serve as a guide to those concerned with framing such national laws and regulations.
Keywords: Fisheries,Fishing boats,Nghề cá,Tàu đánh cá; Safety measures,Safety measures,Biện pháp an toàn,Biện pháp an toàn